1997
DOI: 10.1111/1467-9957.00044
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Money in Greece: Further Empirical Results and Policy Implications

Abstract: In this paper we investigate the determinants and the stability of the demand for broad and narrow de¢nitions of money in Greece. The demand for M2 has not been previously studied. The ¢ndings of the empirical work suggest that the demand for M1 is unstable. For M2 the results presented are not su¤ciently unambiguous to provide a basis for a policy prescription in favour of the adoption of a monetary target. In terms of anti-in£ation policy e¤ciency, it is argued that a potentially better policy choice for Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“… Previous studies of Greek money demand, using narrower aggregates, report the following elasticities. Papadopoulos and Zis (1997) obtain elasticities of 1.49 for M1 and 2.04 for M2. Karfakis (1991) and Psaradakis (1993), both using M1, obtain elasticities of 1.15 and 1.45, respectively.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“… Previous studies of Greek money demand, using narrower aggregates, report the following elasticities. Papadopoulos and Zis (1997) obtain elasticities of 1.49 for M1 and 2.04 for M2. Karfakis (1991) and Psaradakis (1993), both using M1, obtain elasticities of 1.15 and 1.45, respectively.…”
mentioning
confidence: 82%
“…Section III presents the theoretical model. Although recent empirical work on money demand in Greece has mainly focused on the behaviour of the narrower aggregates (Karfakis, 1991; Psaradakis, 1993; Papadopoulos and Zis, 1997), 4 the monetary aggregate used for estimation in this paper is M3, which served as the main aggregate guiding the conduct of monetary policy for much of the period under consideration. Section IV describes the estimation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…We do not make any seasonal adjustment to the data prior to empirical implementation using existing standard methods of de-seasonalization. As has been noted byPapadopoulos and Zis (1997), the use of seasonally unadjusted data has an advantage in that the dynamic properties of the model are not distorted.…”
mentioning
confidence: 99%
“…Similarly, Nagayasu (2003) obtained a near-unit income elasticity estimate of M2 demand for Japan over the 1958-2000 period and, through application of Hansen's (1992) stability tests, revealed that M2 demand is unstable. Papadopoulos and Zis (1997) investigated the determinants and the stability of money demand (M1, M2 and M3) for Greece. Although they find that M2 and M3 are largely stable, they also obtain results which suggest that M1 demand is unstable; this corroborates earlier findings of Sharma (1994).…”
Section: Advanced Countriesmentioning
confidence: 99%